Individual dipole toroidal states: Main features and search in the (e, e') reaction - Nesterenko, V. O.; Repko, A.; Kvasil, Jan; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2019)
Individual low-energy E1 toroidal and compressional states (TS and CS) produced by the convective nuclear current j(c) were recently predicted for Mg-24 in the framework of quasiparticle random-phase approximation (QRPA) with Skyrme forces. In the present QRPA study with Skyrme parametrization SLy6, we explore in more detail properties of these states [toroidal and compressional responses, current distributions, and transitions probabilities B(E1K, 0(+)0 -> 1(-)K), B(E3K, 0(+)0 -> 3(-)K), and B(M2K, 0(+)0 -> 2(-)K) with K = 0 and 1] and analyze the possibility to discriminate and identify TS in inelastic electron scattering to back angles. The interplay of the convective j(c) and magnetization j(m) nuclear currents is thoroughly scrutinized. A two-step scheme for identification of TS in (e, e') reaction is proposed. The key element of the scheme is the strong interference of the orbital and spin contributions, resulting in specific features of E1 and M2 transversal form factors.
CRIS-Team WoS Importer:2019-12-13